A review of corporate goals of No Net Loss and Net Positive Impact on biodiversity. Issue 2 (13th May 2014) - Rainey, Hugo J.; Pollard, Edward H. B.; Dutson, Guy; Ekstrom, Jonathan M. M.; Livingstone, Suzanne R.; Temple, Helen J.; Pilgrim, John D.
Abstract: Increased recognition of the business case for managing corporate impacts on the environment has helped drive increasingly detailed and quantified corporate environmental goals. Foremost among these are goals of no net loss (NNL) and net positive impact (NPI). We assess the scale and growth of such corporate goals. Since the first public, company-wide NNL/NPI goal in 2001, 32 companies have set similar goals, of which 18 specifically include biodiversity. Mining companies have set the most NNL/NPI goals, and the majority of those that include biodiversity, despite the generally lower total global impact of the mining industry on biodiversity compared to the agriculture or forestry industries. This could be linked to the mining industry's greater participation in best practice bodies, high-profile impacts, and higher profit margins per area of impact. The detail and quality of present goals vary widely. We examined specific NNL/NPI goals and assessed the extent to which their key components were likely to increase the effectiveness of these goals in benefiting biodiversity and managing business risk. Nonetheless, outcomes are more important than goals, and we urge conservationists to work with companies to both support and monitor their efforts to achieve increasingly ambitious environmental goals.